Evaluation of the demographic characteristics and general health status of earthquake survivors affected by the 2023 Kahramanmaraş earthquake; a section from Gaziantep Nurdağı district - Leman Tomak; Tolga Demirel; Ibrahim Demir (BMC, 2024)
Abstract Background An earthquake with a magnitude of 7.7 occurred in Pazarcık District of Turkey at 04.17 on February 6, 2023 and another earthquake of 7.6 occurred at 13.24 on the same day. This is the second largest earthquake to have occurred in Turkey. The aim of this study is to investigate the earthquake-related level of knowledge, attitudes and behaviours, general health and psychological status of survivors who were affected by the 2023 Kahramanmaraş Earthquake and who were living in Nurdağı District of Gaziantep after the earthquake. Methods Data of 2317 individuals older than 18 years of age who were living in earthquake neighbourhoods, tents and containers in Nurdağı District of Gaziantep were examined. Variables were evaluated to find out the demographic characteristics and general health status of earthquake victims. General Health Questionnaire (GHQ-12) was used to find out psychological states of earthquake victims. Results The rate of injuries was 14.2% and leg and foot injuries were the most common with 44.2%. The relationship between injury status; and age, marital status, and being trapped under debris was revealed (p < 0.05). Mean GHQ-12 score of the survivors was 3.81 ± 2.81 and 51.9% experienced psychological distress. In the evaluation with logistic regression, it was found that female gender, being injured in the earthquake, loss of first degree and second degree relatives (with a higher rate in loss of first degree relative), having a severely damaged -to be demolished house and having a completely destroyed house were correlated with higher level of psychological distress (p < 0.05). Conclusion General characteristics, injury prevalence and affecting factors of earthquake survivors were evaluated in the present study. Psychological distress was found in victims. For this reason, providing protective and assistive services to fight the destructive effects of earthquake is vital. Accordingly, increasing the awareness of people residing in earthquake zones regarding earthquakes is exceptionally important.